Resistencia del frijol al ataque del gorgojo pardo Acanthoscelides obtectus (Say, 1831) (Coleoptera: Chrysomelidae) en la zona Norte de Sinaloa - Armenta-López, Arturo Rafael; Lugo-García, Gabriel Antonio; Sánchez-Soto, Bardo Heleodoro; Romero-Félix, Celia Selene; Cortez-Mondaca, Edgardo; Nava-Pérez, Eusebio (Instituto de Ecología, A.C., 2021)
The bean is a basic product in the diet of Mexicans, but its commercialization and establishment is affected by the brown weevil (A. obtectus), since it is a serious pest when the seed is stored. In the last decade, in Sinaloa, Mexico, new bean varieties have been established with valuable agronomic characteristics, such as high productivity and quality of the harvested product; However, it is essential to determine the resistance or high tolerance of these cultivars to the attack of this insect. Due to this, the resistance of six bean cultivars (Aluyori, Azufrasin, Azufrado Higuera, Azufrado Noroeste, Azufrado Regional 87 and Janasa) cultivated in the center and north of the state of Sinaloa, to the attack and damage of the bean weevil Acanthoscelides obtectus (Say, 1831) was determined. Six cultivars with four replications were compared. The Aluyori cultivar presented greater resistance with only 18 % seed, low number of emerged adults (37) and minimal decrease in germination capacity (2.33 %). On the contrary, the most susceptible was Janasa with the following values: 51.75 %, 131.5 and 24.75 %, respectively. Therefore, the use of Aluyori and Azufrado Higuera is recommended to reduce the negative impact of the pest, although it is recommended to continue with the experimentation of the materials contained in the germplasm banks for the future release of new cultivars.